2009
DOI: 10.1111/j.1399-6576.2009.02016.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of intra‐operative awareness during general anesthesia in China: a multi‐center observational study

Abstract: The incidence of intra-operative awareness in China is approximately 0.41%, two to three times higher than that widely cited in Western countries. Inappropriately light anesthesia, and the population proportion of surgery and general anesthesia in China may account for the difference. (ClinicalTrials.gov Identifier, NCT00693875.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 30 publications
2
64
2
3
Order By: Relevance
“…In a small study of our own patients, we found that mean INR remained below 1.4 and platelet counts above 150 9 10 9 .l À1 for up to 10 days postoperatively [4]. Other authors have reported more profound derangement.…”
mentioning
confidence: 44%
“…In a small study of our own patients, we found that mean INR remained below 1.4 and platelet counts above 150 9 10 9 .l À1 for up to 10 days postoperatively [4]. Other authors have reported more profound derangement.…”
mentioning
confidence: 44%
“…Volatile anesthetics were used in the control group, but quite often, such as during cardiac surgery, anesthesia had been maintained by total intravenous anesthesia (TIVA). Under these circumstances, one cannot use ETAC for anesthesia depth control, and TIVA alone can be a risk for AWR [50,51]. In 5,000 surgical patients who underwent TIVA [52], BIS monitoring reduced the incidence of awareness compared to the control group (0.14 % vs. 0.65 %, respectively).…”
Section: Eeg-based Monitoring To Prevent Intraoperative Awareness Durmentioning
confidence: 99%
“…In essence, the investigators were sampling from the population of all general anaesthesia survivors from 1946 to the present, who had not previously reported any intra-operative recall, and who had also chanced to be exposed to the investigation team. Despite the lack of a gold standard, our opinion is that studies that have systematically questioned every patient in the populations studied [8][9][10][11][12][13] are likely to have produced more accurate estimates of AAGA incidence than the nationwide NAP5 audit. There is potentially a big difference in reliability in an audit project that depends on reports that can be provided relatively accurately by clinicians (e.g.…”
Section: Essential Findingsmentioning
confidence: 99%